THE PROSPECT OF USING SMART DUSTBIN FOR REDUCING GARBAGE PICK UP TIME (A SIMULATION IN PADANG CITY) - Muhammad Yeza Baihaqi; Wilbert Wijaya; M. Arwin Renardi Widyoko; Temmy Wikaningrum (Journal of Environmental Engineering and Waste Management, 2018)
Service on garbage pick-up is an obligatory service which, should be provided by the goverment. Due to human’s active mobility, which doing activities that may result in waste, that may cause bad impact on the environment and also human themselves. However, the service cost for garbage pick up is not that affaordable, in which government is required to do efficiency, especially to efficient in terms of time. In this study, the place that was used as sample is Padang City. In Padang City, the time that needed to pick-up the garbage from the time the trucks start the trip from the shelter, up to each pick-up point and drop it to the landfill site takes around 6.97 hours. This data is a secondary data that  obtained by previous researchers. In this study, the time simulationhas been elaborated  by replacing the conventional garbage bin to smart dust bin. Smart dustbin is equipped with sensor to count how much garbage inside it and other types of sensor are also equiped to accommodate its work. In addition, Smart Dustbin also equiped with GSM module to send information for indicating that the garbage bin has full. A simulation result showed that using smart dustbin can reducing the pick up time according to the pick-up points  that informed by the GSM module.